Advances in the 1,2-Metalate Rearrangement Chemistry of Alkenylboronates - Tran, Minh-Khoa; Ready, Joseph M. (Synlett, 2025)
Synthetic methods that involve the formation of multiple bonds in a one-pot fashion have played a crucial role in organic chemistry. However, many features of these approaches are still limited, such as stereocontrol and chemoselectivity, especially when nonadjacent stereocenters are formed. Herein, we outlined our efforts in addressing these challenges by advancing the 1,2-metalate shift of alkenylboronic esters.1 Introduction2 1,2-Migration Strategy on Nitrogen-Containing Heterocyclic Substrates3 Enantioselective Allylation with Metal(π-Allyl) Intermediates4 Conclusion
Keywords: boronic esters; dearomatization; allylation; 1,2-migration